Nordijsko obrambno sodelovanje v luči mednarodne varnosti - Raduha, Jurij (Vojaškošolski zbornik, 2024)
This article critically examines the role, importance and impact of the Nordic Defence Cooperation (NORDEFCO) on the global international order and security. The findings show that NORDEFCO is an example of a successful international defence cooperation influencing both the Nordic region and a broader international area. Today, the organization is an important international actor, as the Nordic-Baltic-Arctic area has become an important strategic region for military and geographical reasons, while also constituting a geographical border between NATO and Russia. NORDEFCO's main objective is to meet the Russian challenge in order to ensure the security of Northern Europe, which can be achieved by improving the Nordic countries' capacity for joint military action in crisis and war situations, in conjunction with NATO.
Keywords: international defence cooperation; Mednarodne organizacije; Mednarodni odnosi; mednarodno obrambno sodelovanje; Nato; NORDEFCO; Nordic countries; nordijske države; Regionalizem (mednarodna skupnost); security community; varnostna skupnost; Vojaška politika